Beyond technical learning: Internship as a liminal zone on the way to become a psychologist. (March 2021) - Mele, Enrica; Español, Alicia; Carvalho, Brena; Marsico, Giuseppina
Abstract: The internship has become an essential part of university education. In many curricula, internships are a driving force for professional training and theoretical-practical integration. However, other processes and relational dynamics concerning the trainees' experience have an impact on learning. In this paper, we focus on the educational process between the academic system and the professional world, conceptualizing internship as a border zone. We try to explore the psychological and educational dimensions of the internship, with special attention to the meaning-making process, the affective aspects and the professional identity. Nine female psychology trainees in four different countries (Brazil, Denmark, Italy and Spain) were interviewed while doing their internship. The interview was complemented with various tasks aimed at addressing in depth the interviewees' personal experience. As main results, we highlight how the internship is conceived as an element of separation and continuity in professional development, the experience of ambivalence and insecurity in between the student and professional roles, the relevant role of the tutor, the reflection and imagination as main strategies in the transferring theoretical and practical knowledge and the crucial role of emotions in the process of becoming a psychologist. These elements characterize the internship as a liminal zone, where multiple internal filters regulate the ongoing learning process. The student's reflection emerges as a privileged tool to achieve these results. In this vein, some proposals are presented to improve the integration of the different types of knowledge that come into play in this transitional period.